The Influence Of Job Satisfaction And Leadership On Employee Loyalty At PT. Elap, Empat Lawang Regency - Yodista Yodista; Neri Susanti; Kimas Kurniawan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of job satisfaction and leadership on employee loyalty, both partially and simultaneously. The method used is a quantitative approach with PT ELAP employees as the research object. The results of the study are expected to provide theoretical contributions in the development of human resource management science and practical benefits for companies in designing strategies to increase employee loyalty. This study is limited to the variables of job satisfaction, leadership, and employee loyalty based on the theories of Sallas-Valilla (2021), Northouse (2021), and Ariani (2023), with a focus on the context of local private companies in Empat Lawang Regency. The research sample includes all 47 PT ELAP employees, who were sampled using a census method to obtain comprehensive results. Data were analyzed through validity tests, reliability tests, multiple linear regression, t-tests (partial), F-tests (simultaneous), and coefficients of determination (R²) to determine the effect of independent variables on the dependent variable, both partially and simultaneously. The results of this study prove that high job satisfaction and effective leadership can increase employee loyalty at PT ELAP, Empat Lawang Regency. Practically, companies are advised to improve employee well-being, strengthen leadership qualities, and create a positive work environment to foster employee commitment and retention. Academically, this research contributes to the development of human resource management, particularly regarding the role of job satisfaction and leadership in building long-term employee loyalty.